Radiation dose and cancer induction risk from diagnostic mammography in Dubai tertiary hospital - Noor, Kaltham Abdulwahid; Norsuddin, Norhashimah Mohd; Che Isa, Iza Nurzawani; Murat, Husain; Abdul Karim, Muhammad Khalis (Elsevier Ltd, 2025)
This study aimed to estimate radiation dose and to assess the probability of cancer induction risk among patients who underwent mammography procedure in tertiary hospital in Dubai. After obtained approval from the research ethic committee,155 female patients with an average age of 55.5 ± 12.7 years-old were selected as subjects. Acquisition parameter, tube potential, tube current, compression force, and entrance dose were recorded and analyzed. The Mean Glandular Dose (MGD) were determined by applying the Dance formula, considering the entrance surface air kerma (ESAK) and other conversion coefficients. Patient age-data was used to assess the cancer induction risk from the acquisition, based on Biological Effects of Ionizing Radiation VII (BEIR VII) report, and standardizing the breast thickness. The MGD ranged between 0.7 and 3.5 mGy for medio-lateral oblique (MLO) and for cranio-caudal (CC) projections, respectively. The median MGD for CC lies between 1.4 mGy and 2.1 mGy, with an average of 1.7 mGy. Additionally, the MGD for the 3rd quartile spans a two-fold range. In a population of 100,000 exposed to MLO projection, the cancer incidence risk for a 37-year-old female was 6 times higher than that of a 60-year-old female, at 3.2 out of 100,000 and 0.5 out of 100,000, respectively. The LAR for the 35–45 years age group is 1.91 ± 0.66, decreasing to 0.27 ± 0.07 for those over 65 years. The CC view also shows a decrease from 1.73 ± 0.57 to 0.23 ± 0.04. The mammographic screening radiation dose and the risks that have been found in Dubai all fall within the recommended range, thereby calling for more works of research to determine the progress made in radiation protection. The study has provided additional evidence that the radiation dose used in current practice can be improved.